Resiliência, resistência e tensão: estratégias psicossociais de professores para o enfrentamento do mal-estar docente - Costa, Diana Pereira (2019)
This study focuses on teacher malaise and seeks to investigate strategies of resilience and resistance developed by teachers of a school in the East Zone of the city of São Paulo, a region with socioeconomic vulnerability, based on their social representations of beeing teachers. It is part of the larger study, entitled "Resilience and porosity of city borders: a psychosocial investigation in three Brazilian cities", funded by Research Councils UK and Newton Fund, through a partnership with the National Council of State Foundations for Research Support. Initially, through a literature review, the study undertook the search for the etymology of the words "resistance" and "resilience" in the natural sciences, in which applications date back to the 15th century with Leonardo da Vinci and the 16th century , with Galileo Galilei, and sought to understand the transposition of such concepts to the social and human sciences, in order to identify, in the available specialized literature on the subject, possible links between these concepts and that of teacher malaise. As a result, it was possible to consider the possibility of studying resistance and resilience, as far as teaching work is concerned, from the binomial welfare and teacher malaise. From this point on, the study turned to the characterization actions of the school in a context of socioeconomic vulnerability and to the consultation of teachers, through two focus group sessions, in order to capture elements of teachers' social representations about their profession, representations that have been understood as access routes to the understanding of strategies developed by them to deal with teacher malaise. After the focus group sessions, the data were systematized according to the content analysis procedures. The thematic categories identified pointed to a pessimistic view of the teaching performance, indicating the need for teachers to reflect on the teacher identity, in order to elaborate strategies to deal with the conflicting situations of daily life.